Using solvent effects to guide the design of a CL-20 cocrystal1. Issue 7 (21st February 2015) - Urbelis, Jessica H.; Young, Victor G.; Swift, Jennifer A.
<x xml:space="preserve">Abstract</x> The crystal structure and thermal properties of a 1 : 2 cocrystal of the energetic material CL-20 and triphenylphosphine oxide is reported.